Investigation of the effect of fabric properties on the fabric use efficiency - (:unkn) unknown (My University, 2018)
There are several factors affecting fabric usage efficiency, one of them is fabric properties. The usage of different fabrics for production of the same product increases or decreases the amount of fabric needed, which affects the cost of the product. In this study, effect of fabric properties on the fabric usage efficiency was investigated. For the application processes, 3 different fabrics properties and 3 different garments were used and totally 9 marker plans were prepared. By analyzing the prepared marker plans fabric usage ratios were obtained and effect of fabric properties on the fabric usage efficiency was investigated.